Contents of carboxylic acids and two phenolics and antioxidant activity of dried Portuguese wild edible mushrooms - Ribeiro, Bárbara (2006)
The organic acids and phenolics compositions of nine wild edible mushrooms species ( Suillus bellini, Tricholomopsis rutilans, Hygrophorus agathosmus, Amanita rubescens, Russula cyanoxantha, Boletus edulis, Tricholoma equestre, Suillus luteus, and Suillus granulatus) were determined by HPLC-UV and HPLC-DAD, respectively. The antioxidant potential of these species was also assessed by using the DPPH¥ scavenging assay. The results showed that all of the species presented a profile composed of at least five organic acids: oxalic, citric, malic, quinic, and fumaric acids. In a general way, the pair of malic plus quinic acids were the major compounds. Only very small amounts of two phenolic compounds were found in some of the analyzed species: p-hydroxybenzoic acid (in A. rubescens, R. cyanoxantha, and T. equestre) and quercetin (in S. luteusand S. granulatus). All of the species exhibited a concentration-dependent scavenging ability against DPPH¥. T. rutilansrevealed the highest antioxidant capacity.